Cultural Politics in the Cold War Context: Political Discipline and Institutional Demise at Yenching University - ZHUO, Huili (Journal of Research for Christianity in China (JRCC), 2025)
Since the establishment of the new regime, the fate of Yenching University has been closely intertwined with changes in the international landscape and domestic political transformations. Following the campaigns of “Thought Reform,” the “Three-Anti Campaign,” and the “Campaign for Loyalty and Honesty,” Yenching’s academic and political orientations underwent dramatic realignments. These movements not only dismantled the American-style educational system administratively and shifted toward a Soviet-influenced model emphasizing specialization and practicality, but also profoundly reshaped the ideology of faculty and students through repeated collective study sessions, self-criticism, confessional meetings, and denunciation assemblies. This process ultimately paved the way for the administrative restructuring and closure of Yenching University. By examining the university's experience of political discipline, this paper explores the distinctive role and fate of Christian universities within China’s higher education and cultural policies. The political transformation of Yenching University not only reflects the rupture in Sino-Western relations within the Cold War context but also reveals how the logic of state governance deeply permeated the cultural and educational fields, offering important insights into the mechanisms of political control and cultural policy shifts in the early years of the People’s Republic of China.